Measuring interpersonal trauma: development and validation of the German version of the victimization experience schedule (VES) - Drusko, Armin; Renz, Malika; Schmidt, Hannah; Rosin, Michelle; Simon, Joe J.; Beiner, Eva; Charalambides, Monica; Meyer-Lindenberg, Andreas; Treede, Rolf-Detlef; Tost, Heike; Tesarz, Jonas (Journal of psychosomatic research, 2024)
Objective - Interpersonal victimization experiences (VEs) significantly affect mental and physical health, particularly in disorders associated with life-time adversities, like fibromyalgia syndrome (FMS) and major depressive disorder (MDD). However, assessing VEs comprehensively remains challenging due to limited tools that encompass sub-traumatic events, such as bullying or discrimination, and contextual dimensions. We aimed to address this gap by validating the Victimization Experience Schedule (VES) in German, examining its reliability, and assessing VEs in clinical populations with FMS and MDD. - Methods - We investigated the relationship between VEs and clinical symptoms in individuals with FMS, MDD and healthy controls (N = 105) in a case-control study. We also analyzed correlations between different types of VEs and categories of early childhood abuse and posttraumatic-stress-disorder instruments. Additionally, we validated our findings in an independent sample of individuals with FMS (N = 97) from a clinical study. - Results - We observed excellent inter-rater reliability (Kw = 0.90-0.99), and VEs assessed using the VES were in alignment with subcategories of early childhood abuse. The prevalence of VEs extended beyond the categories covered by traditional survey instruments and was higher in individuals with MDD (4.0 ± 2.6) and FMS (5.9 ± 3.1) compared to controls (1.5 ± 1.7). We consistently identified a significant association between the number of VEs, the associated subjective distress, and clinical scores. Furthermore, distinct correlation patterns between VEs and clinical outcomes emerged across different cohorts. - Conclusion - Our study emphasizes the VES's value in understanding VEs within MDD and FMS. These experiences span from traumatic to sub-traumatic and correlate with posttraumatic-stress and clinical symptoms, underscoring the VES's importance as an assessment tool.
Gesehen am 09.09.2024